Synthesis of phosphorus-containing flame retardants and investigation of their flame retardant behavior in textile applications - Kanat, Muhammed; Eren, Tarik (WILEY, 2019)
Flame retardants are a growing area of research interest. Nonhalogenated, durable, and nonleachable flame retardants are one of the main strategies used in the research of flame retardant polymers. In this regard, the covalent attachment of phosphorus-containing flame retardants onto cotton fabric has been developed. Two types of reactive phosphorus-containing flame retardants (MKT-1 and MKT-2) have been synthesized and used as a surface coating for cotton fabric. MKT-1 possesses anhydride and acid functionalities that can react with the-OH functionalities in cellulose. In addition, MKT-2 has both acid and organosilicon groups that can also react with the hydroxy group present in cellulose. The structures of the reactive flame retardants (MKT-1 and MKT-2) were characterized using C-13 and P-31 nuclear magnetic resonance spectroscopy. Thermal properties of the coated and uncoated cotton fabrics were investigated using thermogravimetric analysis. Surface characterization was carried out using scanning electron microscopy and X-ray photoelectron spectroscopy. A standard test method used to evaluate the flammability of blankets (BS 5852) was also applied to characterize the fire retardant properties of the coated and uncoated cotton fabrics studied. Different loadings of MKT-1 and MKT-2 on the fabric (10, 20, and 30% by weight in dimethylformamide solution) were applied in the dip coating process. The cotton fabric coated with 30% MKT-2 does not burn after being subjected to a propane burner for 20 s and also produced the highest char yield (36%) at 500 degrees C. Inductively coupled plasma-optical emission spectrometry showed that MKT-1 contains 8.23 +/- 0.33 P% whereas MKT-2 contains 3.88 +/- 0.15 P%. Although MKT-1 possess a higher P content than MKT-2, the additive effect caused by the organosilicon and nitrogen groups present in MK-2 enhance its flame retardant properties. Furthermore, the covalently attached flame retardant materials are durable and do not hydrolyze during washing. The mechanical properties of coated fabrics were characterized by a tensile test and significant change in elongation at break was observed. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47935.
Keywords: aminosilanes; cotton-based fabrics; dip coating process; flame retardancy; phosphorus-containing flame retardants; FLAMMABILITY; COTTON; Polymer Science